From benzene to naphthalene: direct measurement of reactions and intermediates of phenyl radicals and acetylene. Issue 40 (4th October 2019) - Chu, Te-Chun; Buras, Zachary J.; Smith, Mica C.; Uwagwu, Awele B.; Green, William H.
Abstract : First-time measurement of time evolution of the main products and critical intermediates on phenyl HACA pathways with a validated pressure-dependent model. Abstract : Hydrogen-abstraction–C2 H2 -addition (HACA) is one of the most important pathways leading to the formation of naphthalene, the simplest two-ring polycyclic aromatic hydrocarbon (PAH). The major reaction channels for naphthalene formation have previously been calculated by Mebel et al., but few experiments exist to validate the theoretical predictions. In this work, time-resolved molecular beam mass spectrometry (MBMS) was used to investigate the time-dependent product formation in the reaction of a phenyl radical with C2 H2 for the first time, at temperatures of 600 and 700 K and pressures of 10 and 50 Torr. A pressure-dependent model was developed with rate parameters derived from Mebel et al. 's calculations and from newly calculated pathways on the C8 H7 PES at the G3(MP2, CC)//B3LYP/6-311G** level of theory. The model prediction is consistent with the MBMS product profiles at a mass-to-charge ratio ( m / z ) of 102 (corresponding to the H-loss product from C8 H7, phenylacetylene), 103 (the initial C8 H7 adduct and its isomers plus the 13 C isotopologue of phenylacetylene), 128 (naphthalene), and 129 (C10 H9 isomers plus the 13 C isotopologue of naphthalene). An additional C8 H7 isomer, bicyclo[4.2.0]octa-1, 3, 5-trien-7-yl, not considered by Mebel et al. 's calculations, contributes significantly to the signal at m / z 103 due to its stable energy and low reactivity. At high C2 H2 concentrations, bimolecular reactions dominated the observed chemistry, and the m / z 128 and m / z 102 MBMS signal ratio was measured to directly determine the product branching ratio. At 600 K and 10 Torr, branching to the H-loss product (phenylacetylene) on the C8 H7 PES accounted for 7.9% of phenyl radical consumption, increasing to 15.9% at 700 K and 10 Torr. At 50 Torr, the branching was measured to be 2.8% at 600 K and 6.2% at 700 K. Adduct stabilization is favored at higher pressure and lower temperature, which hinders the formation of the H-loss product. The pressure-dependent model predicted the observed branching ratios within the experimental uncertainty, indicating that the rate parameters reported here can be used in combustion mechanisms to provide insights into phenyl HACA reactions and PAH formation.